Harry the homeless puppy (holly webb animal stories) webb, holly and williams, sophy - Webb, Holly (Stripes New York, 2009)
Grace can't have a puppy of her own, but she loves walking the dogs at the local animal shelter; her favourite is Harry, a lively Jack Russell puppy.Harry loves going for walks with Grace, and soon the two are best friends. But then Harry is rehomed and Grace is heartbroken. Grace knows she should be pleased that Harry has a home of his own, but she misses him terribly...and poor Harry doesn't understand at all - where has his beloved Grace gone?